The 50-year-old Oil Crisis and its Impact on the Global Economy: A Bibliometric Analysis - Mim, Tahmina Akther; Kathiravan, Chinnadurai; Maniam, Balasundram (International Journal of Energy Economics and Policy, 2024)
The world faced different crises, several times, in the last five decades. The COVID-19 pandemic, debt crisis and oil bubble were the most important crises among them. During the crisis, the main financial driving factor was the oil price which transmitted an alarming hit to other economic nexus factors. The objective of this paper was to find out the crisis period, caused by crude oil and its eventuality in different markets’ historical plots. Scopus data represent 605 studies, using the bibliometrix R tool, about crude oil and related crises. Within the context of the contemporary scientific literature, the most significant authors, publications, and research institutions were included in this paper. In the context of the most recent scientific literature, the most significant authors, publications, and research institutions were identified and the relevance of their contributions was established. This research employed disaggregated sectoral analysis and mechanistic analysis on grounded theory, which included moderation analysis. Finally, this bibliometric analysis tried to locate roadblocks in the current literature as well as indicate new directions for investigation.